DEVELOPING A TOLERANT WORLDVIEW IN PRIMARY SCHOOL STUDENTS: THEORETICAL AND PRACTICAL APPROACHES (Scientific journal of the Fergana State University, 2025)
This article focuses on studying the issue of developing a tolerant worldview in primary school students based on theoretical and practical approaches. The research analyzes the social and cultural foundations of the concept of tolerance, as well as how it is reflected in different languages and cultures. The psychological and pedagogical aspects of tolerance are also examined, as they play an important role in children's socialization and the assimilation of cultural codes. The article describes methods for fostering tolerance through children's games and forming qualities such as readiness for compromise and respect for others' opinions. Practical recommendations and strategies for promoting tolerance in the modern education system are also presented. The research findings will assist teachers and education specialists in shaping a culture of tolerance among primary school students. Thus, the article highlights the importance of both theoretical knowledge and practical applications. The study employed theoretical, comparative, and practical methods of analyzing the concept of tolerance. These methods help assess the effectiveness of games and educational activities in developing children's social and cultural skills. The comparative analysis identified similarities and differences in the concept of tolerance across various languages and cultural contexts.